KONSEP MANAJEMEN PERGURUAN TINGGI KEAGAMAAN ISLAM (PTKI) - Ali Mustopa Yakub Simbolon; Ira Yanti; Weni Sumarni; M. Arif (Jurnal Dedikasi Pendidikan, 2023)
The success of Islamic figures in education is demonstrated by the continued existence of Islamic Religious Colleges (PTKI). This effort was carried out with various breakthroughs in order to survive. This study aims to describe the management concept of Islamic Religious Higher Education (PTKI). The method used in this study is qualitative with the type of library research (Library Research). Sources were obtained from online-based books, books and scientific articles from Google Scholar. Based on the research findings that Islamic Religious Higher Education Management (PTKI) is an Islamic higher education institution management through commanding, coordinating, controlling, and other management functions carried out through interpreting, coordinating resources existing resources to achieve the goals and objectives of Islamic Higher Education effectively and efficiently. Management based on Al-Quran and Hadith is his trademark. This basis is a differentiator from management outside the Islamic Religious College (PTKI). PTKI presents the ideology of sincerity, honesty, trust, justice and responsibility, by integrating management functions in general. This answers the challenges of the times from the past until now.